Impacts of Wildlife Conservation Education Effort on Selected Communities surrounding Kainji Lake National Park, Nigeria - Halidu, S. K.; Fingesi, U. I.; Akinola, O. O. (NIU Journal of Social Sciences; Vol 9 No 2 (2023): NIU Journal of Social Sciences, Vol. 9 No. 2, June 2023, 2023)
This study focused on the Impacts of Wildlife Conservation Education Effort on Selected Communities Surrounding Kainji Lake National Park was undertaken to derive information on the communities’ level of knowledge and attitude as well as impact of education programs towards wildlife conservation in the area.  The methodology employed in the study includes the use of structured questionnaire and oral interviews to acquire information from sampled members of the communities on the on the impact conservation education in their area. The data collected were analyzed using descriptive statistics- tables, charts and percentages. Non-parametric Chi-square χ 2 test was used to evaluate the significance of differences between data sets at 0.05 significance level. The results gathered revealed that majority of the respondents across the communities are aware of conservation education in their area. The chi-square test showed that the proportion of awareness is significantly different *(P<0.05) between those who are aware and those who are not. Participation in the conservation program influenced the behavior of members of the communities; it increases the peoples understanding of wildlife management with 98.66% across the community saying yes and 98.66% respondents declaring interest in wildlife conservation. Hence there is significant relationship between communities’ level of knowledge and their impact on the protection and conservation of park resources. It is therefore recommended that government should create more awareness on wildlife conservation through education programs and workshops so as to help minimize illegal activities in the park. Keywords: Impacts, Wildlife, Conservation Education, Communities, Kainji Lake National Park.